2017
DOI: 10.1007/s10096-017-2973-0
|View full text |Cite
|
Sign up to set email alerts
|

The burden and epidemiology of community-acquired central nervous system infections: a multinational study

Abstract: Risk assessment of central nervous system (CNS) infection patients is of key importance in predicting likely pathogens. However, data are lacking on the epidemiology globally. We performed a multicenter study to understand the burden of community-acquired CNS (CA-CNS) infections between 2012 and 2014. A total of 2583 patients with CA-CNS infections were included from 37 referral centers in 20 countries. Of these, 477 (18.5%) patients survived with sequelae and 227 (8.8%) died, and 1879 (72.7%) patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 33 publications
4
59
2
3
Order By: Relevance
“…Despite limited information about the etiological spectrum of febrile encephalopathy in adults, many studies across the world have investigated the etiological spectrum of specific syndromes of CNS infections, including encephalitis syndrome in different populations [ 22 26 ]. A recently published large retrospective multinational study ( n = 2583) has provided information on the etiological spectrum of community acquired CNS infections from 37 referral centers in 20 countries [ 27 ]. The most frequent infecting pathogens reported in this study were Streptococcus pneumoniae and Mycobacterium tuberculosis [ 27 ], which are the same as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited information about the etiological spectrum of febrile encephalopathy in adults, many studies across the world have investigated the etiological spectrum of specific syndromes of CNS infections, including encephalitis syndrome in different populations [ 22 26 ]. A recently published large retrospective multinational study ( n = 2583) has provided information on the etiological spectrum of community acquired CNS infections from 37 referral centers in 20 countries [ 27 ]. The most frequent infecting pathogens reported in this study were Streptococcus pneumoniae and Mycobacterium tuberculosis [ 27 ], which are the same as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…CNSI is still associated with severe neurological complications today. Subdural empyema, brain abscess, and hydrocephaly were among the complications reported by Pişkin et al [15] In a multicenter study by Erdem et al [31] that included 2583 patients, suppurative intracranial infection was detected in 5.6% of the patients, with most cases consisting of brain abscess (n=97), epidural abscess (n=31), and subdural empyema (n=14). In our study, brain abscess, subdural empyema, and hydrocephaly were the most common sequalae.…”
Section: Discussionmentioning
confidence: 99%
“…Demiroğlu et al [12] observed memory disorders and behavioral changes as sequelae in encephalitis patients, and neurogenic bladder and left homonymous hemianopsia in tuberculous meningitis patients. Erdem et al [31] reported the frequency of sequelae to be 18.5%, with the most common sequelae being motor deficit (5%), cranial nerve involvement (3.6%), cognitive disorder (2.7%), persistent headache (1.5%), and epilepsy (1%). Sequelae observed in our study were hemiplegia, hearing loss, and ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a multinational study performed with 2583 patients in 37 referral centers in 20 countries to understand the burden of community-acquired central nervous system infections between 2012 and 2014 [10], staphylococci and Listeria were responsible for frequent infections in immunocompromised patients. In another study of 102 patients on maintenance hemodialysis, of 1402 patients hospitalized for infectious spondylodiscitis over a 13-year period, MRSA was the commonest pathogen found in the infectious sites followed by coagulase-negative staphylococci [11].…”
Section: Prevalence Of Staphylococci In Different Diseased Conditionmentioning
confidence: 99%